The matter of black lives : writing from The New Yorker - Cobb, Jelani; Cobb, Jelani; Remnick, David; Baldwin, James, 1924-1987; Morrison, Toni; Gladwell, Malcolm, 1963-; Cobb, Jelani; Adichie, Chimamanda Ngozi, 1977-; Sanneh, Kelefah; Lee, Andrea; Kincaid, Jamaica; Allen, Danielle S., 1971-; et al. (Ecco, an imprint of HarperCollinsPublishers, 2021)
Bringing together reporting, profiles, memoir and criticism from The New Yorker to present a bold and complex portrait of black life in America, told through stories of private triumphs and national tragedies, political vision, and artistic inspiration throughout history.